Implementasi Crime Prevention Through Environmental Design (CPTED) Pada Fasilitas Parkir Sepeda Motor (Studi Kasus: Kampus Fakultas Ilmu Budaya USU) - Aulia Malik Affif; N Novrial (Diponegoro University, 2021)
Most often crime that occurs on the USU campus is motorcycle theft. In fact, several motorcycle theft on the USU campus is covered by electronic media. So there is a need to make a motorcycle parking model to reducing and preventing the opportunity for crime to occur. This research aims to make a model of Faculty of Cultural Studies USU campus motorcycle parking with the CPTED concept. This research using the descriptive qualitative method. This research started with a physical analysis of existing conditions in the motorcycle parking area, then the author developing a motorcycle parking model with the CPTED concept. The result of this research is motorcycle parking model in Faculty of Cultural Studies USU campus is focusing on six ways, i.e: (1) using hedge as fence; (2) using automated system parking portal and pedestrian way from/to parking area; (3) construct parking lot roofing; (4) construct students gathering space; (5) using speed bump; (6) using signage. By applying this six ways, the Faculty of Cultural Studies USU campus motorcycle parking is expected to free from any crime.